HEROISM OF SAMIRAH AL-ABBAS IN RIORDAN’S THE SHIP OF THE DEAD - Reza Akbar Meidiansyah (PARADIGM: Journal of Language and Literary Studies, 2022)
People tend to associate heroes and heroism with the acts of being brave and risking life. However, actions that have both of these features are far more likely to generate heroic labels than actions that have only one feature. This paper aims to show the heroism of Samirah al-Abbas in the Rick Riordanâ€™s third novel of the Magnus Chase and the Gods Of Asgard trilogy entitled The Ship of The Dead. This paper approaches the heroism values of the character by applying the concept of the Great Eight popularized by George R. Goethals and Scott T. Allison. The findings show that throughout the plot of the book, Samirah exhibited six of eight heroic traits, which are caring, charismatic, inspiring, selfless, smart, and strong.Â